Greco-Roman and Jewish tributaries to the New Testament: festschrift in honor of Gregory J. Riley - Crawford, Christopher S.; Riley, Gregory J. (Claremont studies in New Testament & Christian origins, 2019)
"This volume explores the Greco-Roman and Jewish origins of the New Testament and early Christianity. It pays particular attention to the gospels and the traditions which place those sacred texts."--Publisher statement